Assembly strategies of organic-based imaging agents for fluorescence and photoacoustic bioimaging applications. (4th December 2019) - Cheng, Hong-Bo; Li, Yuanyuan; Tang, Ben Zhong; Yoon, Juyoung
Abstract : The results of numerous studies have led to the development of assembled organic substances for fluorescence and photoacoustic bioimaging as part of comprehensive approaches to the diagnosis of diseases. Abstract : The results of numerous studies have led to the development of supramolecular (assembled) organic substances for use in biomedical imaging as part of comprehensive approaches to the diagnosis of diseases. This review summarizes recent advances that have been made in the design and fabrication of assembled organic dyes for fluorescence and photoacoustic bioimaging.